2020
DOI: 10.3390/biom10040521
|View full text |Cite
|
Sign up to set email alerts
|

Myo-Inositol Transporter SLC5A3 Associates with Degenerative Changes and Inflammation in Sporadic Inclusion Body Myositis

Abstract: Myo-inositol exerts many cellular functions, which include osmo-protection, membrane functioning, and secondary messaging. Its Na+/myo-inositol co-transporter SLC5A3 is expressed in muscle tissue and further accumulates in myositis. In this study we focused on the peculiar subgroup of sporadic inclusion body myositis (IBM), in which auto-inflammatory responses and degenerative changes co-exist. A cohort of nine patients was selected with clinically confirmed IBM, in which SLC5A3 protein was immune-localized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…[ 77 ] Recently, SMIT1 was found in subset of muscle‐infiltrating auto‐aggressive immune cells, of which most were T‐cells and M1 lineage macrophages of clinically confirmed sporadic inclusion body myositis (IBM) patients. [ 78 ] This study reported that higher expression of SMIT1 followed by HMIT expression and negligible expression of SMIT2 in macrophages suggesting significance of SMIT1 and HMIT.…”
Section: Discussionmentioning
confidence: 87%
“…[ 77 ] Recently, SMIT1 was found in subset of muscle‐infiltrating auto‐aggressive immune cells, of which most were T‐cells and M1 lineage macrophages of clinically confirmed sporadic inclusion body myositis (IBM) patients. [ 78 ] This study reported that higher expression of SMIT1 followed by HMIT expression and negligible expression of SMIT2 in macrophages suggesting significance of SMIT1 and HMIT.…”
Section: Discussionmentioning
confidence: 87%
“…SLC5A3 is essential for the maintaining and transporting myo-inositol [ 9 , 23 , 24 ]. We found that SLC5A3 silencing by shRNA (shSLC5A3-S1 or shSLC5A3-S2) or SLC5A3 KO induced robust myo-inositol depletion in pCan-1 primary NSCLC cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of SLC5A3 is likely associated with the pathophysiology of Down syndrome [ 8 ]. De Paepe et al ., have proposed that SLC5A3 is a pathological hallmark that is upregulated in sporadic inclusion body myositis (IBM) tissues, which could be linked to the degenerative changes and inflammation of the disease [ 9 ]. Andronic et al, reported that swelling-mediated activation and upregulation of SLC5A3 promoted myo-inositol transport and regulated hypotonic volume in mammalian cells [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mutations of ZC3H12A had recently been verified to be associated with ulcerative colitis recently (47,48). Besides, SLC5A3 (solute carrier family 5 member 3) was proved to be promote inflammatory responses in inclusion body myositis (IBM) (49). Their up-regulation might further reduce the antitumor immune response.…”
Section: Discussionmentioning
confidence: 99%